Improving Coastal Children Eco-Literacy in Environmental Learning Through Mangroves Storytelling - Novi Utami Rosyid; Budiaman Budiaman; Uswatun Hasanah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
The objective of this research was to determine the level of coastal children eco-literacy by using storytelling about the role of mangroves for coastal communities in Serang Regency - Banten. The research methodology was classroom action research (CAR). The implementation of classroom action research was conducted of two cycles. There was cycle I and cycle II, each cycle consisted of two meetings. This research involved third-grade students which consisted of 30 students in SDN Cerocoh, Serang Regency - Banten. The instrument of the research was data collecting technique, the data were observation, tests (pre-test and post-tests), and documentation. The result of this research showed that there was a significant difference in the students’ eco-literacy in pre-test and post-test after learning environmental education with mangrove storytelling. The average score of pre-test was 48.52%, while, after giving treatment in cycle I, the students average score in post-test I was 68.94%. Then, after giving treatment in cycle II, the students’ average score in post-test II was 87.17%. Based on the data the researcher concluded that: 1) there was the improvement coastal student eco-literacy by using mangrove storytelling in teaching environmental education at our environmental thematic subject 2) the students became interested and motivated in learning about mangroves.